Post-Ugi Cyclization for the Construction of Diverse Heterocyclic Compounds: Recent Updates - Bariwal, Jitender; Kaur, Rupinder; Voskressensky, Leonid G.; Van der Eycken, Erik V. (Frontiers in Chemistry, 2018)
Multicomponent reactions (MCRs) have proved as a valuable tool for organic and medicinal chemist because of their ability to introduce a large degree of chemical diversity in the product in a single step and with high atom economy. One of the dominant MCRs is the Ugi reaction, which involves the condensation of an aldehyde (or ketone), an amine, an isonitrile and a carboxylic acid to afford an -acylamino carboxamide adduct. The desired Ugi-adducts may be constructed by careful selection of the building blocks, opening the door for desired post-Ugi modifications. Such post-Ugi transformations represent extremely powerful synthetic methods for the construction of diverse heterocycles. In recent years, such transformations have expanded rapidly, giving access to various heterocyclic systems. This review outlines the developments achieved in the past few years, highlighting the modifications performed in a sequential or domino fashion, with emphasis on major concepts, synthetic applications of the derived products as well as critical mechanistic aspects.